The Influence of Design Thinking in Entrepreneurship Programs on Entrepreneurial Spirit and Independence of Fifth-Grade Elementary School Students - Sri Hardyanti Puspita Sary; Elpisah Elpisah; Saripuddin Saripuddin; Suarlin Suarlin (International Journal of Educational Development, 2026)
This study aims to: (1) examine the effect of an entrepreneurship program using a Design thinking approach on the entrepreneurial spirit of Grade V students at UPT SPF SD Inpres Baraya 1, Makassar City, and (2) examine the effect of an entrepreneurship program using a Design thinking approach on student independence of Grade V students at UPT SPF SD Inpres Baraya 1, Makassar City. This research employed a quantitative approach with a quasi-experimental method using a Non-Equivalent Control Group Design. The research subjects consisted of two groups: an experimental group that received an entrepreneurship program based on Design thinking and a control group that did not receive the treatment. Data were collected using questionnaires measuring students’ entrepreneurial spirit and independence, supported by documentation. Data analysis was conducted using descriptive statistics, classical assumption tests, and hypothesis testing through an independent samples t-test. The results indicate that the entrepreneurship program using a design thinking approach had a significant positive effect on students’ entrepreneurial spirit and independence. The independent samples t-test revealed that the program significantly improved students’ entrepreneurial spirit (p = 0.002 < 0.05) compared to the control group. Likewise, a very significant effect was found on student independence, with a significance value of p = 0.001 < 0.05. These findings confirm that the application of a design thinking–based entrepreneurship program effectively enhances key entrepreneurial attributes, including creativity, initiative, responsibility, and independence among fifth-grade elementary school students.